PENERAPAN PERAN TOTAL QUALITY MANAGEMENT DAN PENGARUHNYA TERHADAP KUALITAS PELAYANAN PRIMA - Suhermini Suhermini (Jurnal Ekonomi dan Bisnis, 2010)
The objectives of this research are examine the influence of applying Total Qualitative Management(TQM) on the excellent service of the village chief apparatus in Gunungpati Semarang subdistrictand to examine the biggest influences of TQM dimension towards the excellent service.Population of the research is societies 16 kelurahan at Gunungpati Subdistrict Semarang. Thesample consists of 160 societes in Gunungpati Subdistrict Semarang. The research method usethe survey method with questionaire. The examining hypothesis in multi regression under SPSS13.The research result find that there is some influence in apllying TQM on the excellent serviceof the apparatus in kelurahan Gunungpati subdistrict, Semarang. Another examining result whichis done with contrasting the dimension of educational beta value coefficient and the biggest exercisingin contrast with another beta coefficient. It means that the educational dimension andexercising that influencing on the excellent service of the apparatus in kelurahan Gunungpati subdistrict,Semarang. Limitation of this research are the use of survey methods and only GunungpatiSubdistrict to predict excellent service of all kelurahan in Semarang city.Keyword : Total Quality Management, Excellent Service, Educational and Exercising